PENGARUH DOSIS PUPUK FOSFOR DAN KONSENTRASI GIBERELIN PADA PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA (Brassica oleraceea L.) - Rohman, Nur; Widiatmanta, Jeka (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
The flower cabbage (Brassica oleraceea L.) is a type of vegetable plant belonging to the family of cabbage plants (Cruciferae). Flower cabbage often called "cauliflower" has many benefits to consume, because it contains calories, protein, carbohydrates, calcium, and vitamins A, B1 and C. Farming is very much affected by the state of agricultural land, a problem that often occurs due to lack of elemental content nutrients in the soil that affect the inflorescence and flower cabbage growth. Therefore, to increase the yield of cabbage flowers offered the method of land optimization with the addition of nutrients in the form of phosphorous soil and also the addition of gibberellin hormone that has a role to flowering cabbage plants. The research was conducted by using Randomized Block Design (RBD) in divided plots with 2 treatments, Phosphorus (P) as the main plot with 3 treatment levels P1 (100 kg / ha), P2 (125 kg / ha) and P3 150 kg/ha then the concentration of Giberelin (K) as a subplot with 3 levels of treatment K1 (75 mg / L), K2 (100 mg / L) and K3 (125 mg / L)). From the result of the combination of the two treatments were 9 treatment combinations, repeated 3 times to obtain 27 units combination of treatments, each experimental plot consisted of 15 plants. Parameters observed include plant height, number of leaves, number of flowering plants, flower diameter and flower weight. The result of the research showed no significant interaction in all plant variables but the dosage of phosphorus fertilizer gave significant effect on the height variable of the 10 hst plant on the P1 (100 kg/ha) treatment, the leaf number variant showed significant effect at age 40 hst on P3 treatment (150 kg / ha), the number of flowering plant variables showed significant effect of 60 hst on P3 treatment (150 kg / ha), flower diameter variables showed significant differences in P3 treatment (150 kg / ha). The best treatment is P3 treatment (150 kg / ha). Gibberellin concentrations did not have a real effect on all plant variants.